Authenticity in oral communication of instructed L2 learners - Nowicka, Agnieszka; Wilczyńska, Weronika (Multilingual Matters, 2011)
The skill of producing oral discourse in L2 is commonly considered to be difficult to foster in instructional setting. However, the main problem appears to be ensuring an authenticity of speaking both in personal, internal sense and in the social, socio-linguistic dimension. The main claim of here-discussed person centered approach is that both of these dimensions, although distinct, do not need to be treated in L2 learning as systematically separate and incompatible ones. On the contrary, integrating them, the learner creates a solid base of effective and consistent development of competence in L2 spoken discourse. The process requires a will to foster one’s foreign language identity a conscious acceptance of it. It seems equally necessary to use speech realization patterns representing a wide gamut of discourse genres. These actions are not exclusively appropriate only on advanced levels of FL learning – quite the opposite, they should be implemented early on, at the beginning stages of FL learning, even if in the form of developing language and communicative awareness (sensitivity), as a basis of modeling future multilingual communicative competence.
Keywords: FL learning; oral discourse; spoken communication; communicaitve competence; authenticity; conversation analysis